2021
DOI: 10.1111/ppc.12959
|View full text |Cite
|
Sign up to set email alerts
|

Is distance education obligatory or a new trend? The effect of psychiatric nursing e‐course on stigma

Abstract: Purpose To examine the effects of psychiatric nursing e‐course taught by distance learning on students' beliefs about mental illnesses. Design and Methods This study was conducted as a pretest, posttest, and follow‐up quasi‐experimental study with 147 nursing students. Findings The results showed that the psychiatric nursing e‐course significantly reduced the stigmatization total and dimension scale scores of the participants, and the effect continued in the follow‐up measurement. The difference between the pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 22 publications
(31 reference statements)
0
1
0
Order By: Relevance
“…Yet, different results can be encountered in the literature. In a study conducted by Terzioğlu et al (2017), more than half of the participants were younger than the average age of this study, and in a study by Öz and Ayhan (2021), the average age of the group was found to be 21 (Seki Öz & Ayhan, 2021;Terzioğlu et al, 2017). In a study conducted in Spain, 75% of the participants were female, and the average age was 25 (Ramos-Morcillo et al, 2020).…”
Section: Discussionmentioning
confidence: 37%
“…Yet, different results can be encountered in the literature. In a study conducted by Terzioğlu et al (2017), more than half of the participants were younger than the average age of this study, and in a study by Öz and Ayhan (2021), the average age of the group was found to be 21 (Seki Öz & Ayhan, 2021;Terzioğlu et al, 2017). In a study conducted in Spain, 75% of the participants were female, and the average age was 25 (Ramos-Morcillo et al, 2020).…”
Section: Discussionmentioning
confidence: 37%
“…A total of fourteen studies examined the relationship between theoretical education and the stigma of nursing students, finding that nursing students who received more hours of mental health nursing education demonstrated significantly more favorable views and attitudes toward mental health [ 28 ] and even the distance education also proven to yield positive outcomes in shaping student attitudes [ 46 ]. Expert by experience (EBE) involvement in the mental health theoretical course was prevalent, and EBE involvement is used to provide nursing students with an in-depth understanding of the expectations of the mental health consumer perspective and to foster the person-centered perspective.…”
Section: Resultsmentioning
confidence: 99%